Panorama of Nome, 1915 - Curtis, Asahel, 1874-1941 (1915)
On verso of image: Nome. Copies made in 1915 for Alaska Bureau. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number